Perlindungan Hukum Terhadap Kreditur: Tinjauan Komparatif Undang-undang Tentang Fidusia dan Hak Tanggungan - Korua, Jolanda Marlien; Taroreh, Royke Adrianus; Nacrawy, Nurhikmah; Taroreh, Vicky Fransiskus (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
This research is useful in exploring legal protection for creditors in property security law through a comparative study of Fiduciary and Mortgage Laws. Using a normative method, a literature review serves as the primary instrument for collecting secondary data, with primary legal materials in the form of Fiduciary and Mortgage Laws, as well as laws on consumer protection and bankruptcy. Primary sources are supplemented by implementing regulations. Through analysis using legal and conceptual approaches, it was found that both laws provide protection for creditors, which can be further refined with implementing regulations to ensure equitable access to credit or debt and facilitate all parties to remain within the legal protection corridor.